Preliminary Design of a 6-Seater Electric Aircraft - Calvin Chandra; M Khan; T Putri; W Alexsoh; M A Moelyadi; E Amalia (Institut Teknologi Bandung, 2022)
Demands for delivering a more sustainable and eco-friendly aircraft increase for the near future. However, the technology of current electric power for the aircraft (e.g., electric motors and batteries) is still lacking compared to matured power technology using fossil-fuel. A preliminary design of electric aircraft becomes initial important steps to obtain matured fully electric aircraft. This design step requires various analytical and software-based analyses to fullfill the design requirements and objectives. The design requirement of designing electric aircraft is aircraft with maximum take of weight of 5000 equipped with 6-seater. From the design results show that the designed aircraft fulfills all the requirements and most of the objectives. The design itself still need furtherdevelopment through optimization, re-evaluation, future studies, and upcoming technologies.Keywords: Aircraft Design; Electric Aircraft; Sustainability